2016
DOI: 10.1002/stem.2283
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Regulates Hepatocytic Differentiation of Progenitor Cells by Targeting YAP1

Abstract: MicroRNA expression profiling in human liver progenitor cells following hepatocytic differentiation identified miR-122 and miR-194 as the microRNAs most strongly upregulated during hepatocytic differentiation of progenitor cells. MiR-194 was also highly upregulated following hepatocytic differentiation of human embryonic stem cells (hESCs). Overexpression of miR-194 in progenitor cells accelerated their differentiation into hepatocytes, as measured by morphological features such as canaliculi and expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…Although it can be treated by surgery and chemotherapy, the clinical prognosis remains poor. In recent years, many studies have indicated that miRNAs play a role in the development of osteosarcoma, with several miRNAs found to be aberrantly expressed in osteosarcoma development [11-13]. Our study demonstrated that miR-194 may play an antioncogenic role in the development of osteosarcoma.…”
Section: Discussionsupporting
confidence: 58%
“…Although it can be treated by surgery and chemotherapy, the clinical prognosis remains poor. In recent years, many studies have indicated that miRNAs play a role in the development of osteosarcoma, with several miRNAs found to be aberrantly expressed in osteosarcoma development [11-13]. Our study demonstrated that miR-194 may play an antioncogenic role in the development of osteosarcoma.…”
Section: Discussionsupporting
confidence: 58%
“…miR‐194 has been reported to act a great role in numerous physiological and pathological pathways. For instance, overexpression of miR‐194 can decrease stellate cell activation (Venugopal et al, ), modulate hepatocytic differentiation of progenitor cells (Jung et al, ) and osteoblast differentiation (Li et al, ). In addition, miR‐194 is involved in Toll‐Like Receptor 4 Inflammatory Responses in THP‐1 Cells (Tian et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of cell development for producing differentiated and mature cells is based on gene expression and transcriptional regulators. For example, miR‐1 and miR‐133 are modulatory molecules of the skeletal muscle proliferation and differentiation (Chen et al, ), miR‐23a has an inhibitory function on osteogenesis of human bone marrow mesenchymal stem cells (hBM‐MSCs) (Li et al, ), miR‐194 controls hepatocytic differentiation of the progenitor cells (Jung et al, ), and miR‐99b, ‐181a, and ‐181b play essential roles in the differentiation of human embryonic stem cells (hESCs) toward vascular endothelial cells (Kane et al, ), while transfection of hiPSCs with miR‐186 and miR‐375 leads to islet‐like cell clusters differentiation (Shaer et al, ). Differentiation of different sources of cells to islet‐like structures has been reported in several studies and in some cases miRNAs were applied to conduct this differentiation process.…”
Section: Introductionmentioning
confidence: 99%